Secure Exchange of Digital Goods in a Decentralized Data Marketplace - Futoransky, Ariel (2019)
We are tackling the problem of trading real-world private information using only cryptographic protocols and a public blockchain to guarantee honest transactions. In this project, we consider three types of agents —buyers, sellers and notaries— interacting in a decentralized privacy-preserving data marketplace (dPDM) such as theWibson data marketplace. This framework offers infrastructure and financial incentives for individuals to securely sell personal information while preserving personal privacy. Here we provide an efficient cryptographic primitive for the secure exchange of data in a dPDM, which occurs as an atomic operation wherein the data buyer gets access to the data and the data seller gets paid simultaneously.